The Effect of Environmental Technique to the Students Achievement in Learning Vocabulary in Junior High School At Batam - Warno Edi (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2018)
This article is written with title The Effect of Environmental t Technique to the Student Achievement in Learning Vocabulary in Yunior High School  SMPN 30  at Batam. English as an international language is used in countries throughout the World, including Indonesia. Last few years, English has been taught at Junior High School. It has been accepted in Indonesia in line with the government’s plan on the nine-year compulsory study. Based on the 2013 curriculum, English at Junior High School level is taught as local content to serve the need of the local community. In this study, The Writer attempted to use an action research as methodology in teaching English vocabulary to young learners, particularly to the first graders.  In applying this study, the writer use the instruments.The instruments of the study in this research are a Environmental technique, tests, field notes and a questionnaire. After giving all the instrument, the writer analyze the result using statistical formulas. Then the writer compared the results in pre-test and post-test.